2003
DOI: 10.1590/s0034-72992003000200013
|View full text |Cite
|
Sign up to set email alerts
|

Otimização da percepção da fala em deficientes auditivos usuários do sistema de implante coclear multicanal

Abstract: Obj etivo: realizar um estudo intra-sujeito, avaliando o reconhecimento da fala e a preferência subjetiva em deficientes auditivos usuários do sistema de implante coclear (IC) Nucleus 24, nas diferentes estratégias de codificação disponí-veis nesse sistema (Spectral Peak -SPEAK, Continuous Interleaved Sampler -CIS e Advanced Combination Encoders -ACE), a fim de promover a otimização da percepção da fala em cada sujeito. Forma de estudo: Clínico prospectivo. Material e Método: Sete adultos com deficiência audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 8 publications
(8 reference statements)
2
14
0
12
Order By: Relevance
“…In regards to the relation between the speech auditory perception and the speech codification strategies, studies show higher scores on the recognition of phonemes (Psarros et al 2002), words and sentences with the Advanced Combination Encoders (ACE) strategy (Pasanisi et al 2002;Psarros et al 2002;Frederigue and Bevilacqua 2003), either under silence or under noise. Psarros et al (2002) also found improvement of the consonant scores with the ACE strategy, and considered that the improvement of the speech perception obtained with the conversion of the Spectral Peak (SPEAK) strategy to the ACE strategy was significant, and that this improvement was more significant under noise, suggesting that the conversion of the SPEAK strategy to the ACE strategy is beneficial for children, and the ACE strategy may be an initial choice for them.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the relation between the speech auditory perception and the speech codification strategies, studies show higher scores on the recognition of phonemes (Psarros et al 2002), words and sentences with the Advanced Combination Encoders (ACE) strategy (Pasanisi et al 2002;Psarros et al 2002;Frederigue and Bevilacqua 2003), either under silence or under noise. Psarros et al (2002) also found improvement of the consonant scores with the ACE strategy, and considered that the improvement of the speech perception obtained with the conversion of the Spectral Peak (SPEAK) strategy to the ACE strategy was significant, and that this improvement was more significant under noise, suggesting that the conversion of the SPEAK strategy to the ACE strategy is beneficial for children, and the ACE strategy may be an initial choice for them.…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação da percepção de fala através de AASI tem sido bastante estudada (14)(15)(16)(17)(18)(19)(20) . A maioria destes estudos buscou caracterizar a percepção de fala de adultos e crianças deficientes auditivos.…”
Section: Introductionunclassified
“…Speech perception under difficult conditions, such as in the presence of background noise and competitive reverberation (1) , is one of the most significant issues for CI users. One study demonstrated a significant decrease in the performance of deployed speech perception in the presence of background noise (2) , and background noise is the most frequent complaint among CI users (3) .…”
Section: Introductionmentioning
confidence: 99%